Analysis of Sharia Marketing Strategies on The Growth of Halal Product Exports in Indonesia - Devi Salsabilah Putri; Rizkya Sulistyarini (ASEAN Journal of Halal Study, 2024)
This research uses a qualitative method with a descriptive narrative approach to understand the existing situation through an inductive thinking process. The focus of this study is to integrate Islamic principles into sharia marketing strategies for halal product exports in Indonesia. The research method involves an in-depth literature review, including analysis of verses from the Qur'an, hadiths, and relevant regulations issued by the Indonesian Ulema Council (MUI). The research process includes identifying issues, determining subjects, and reflecting on the research results. The findings show that effective sharia marketing strategies can enhance consumer appeal and trust in halal products. Although halal products meet the halal standards according to Islamic law, it is important to consider the implementation of these strategies in the context of international markets. This study emphasizes that marketers of halal products need to pay attention not only to the halal aspect of the products but also to the impact of ethical and transparent marketing practices in building consumer trust.